Menciptakan Generasi Antikorupsi : Pendidikan Antikorupsi Bagi Siswa SD dan SMP Perguruan Advent Parongpong - James Sylvanus Uly Reke; Eddy Thimothi Peranginangin; Faith Cornelia Judd Sinaga (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The implementation of this community service activity aims to foster the development of an anti-corruption generation by emphasizing the early inculcation of anti-corruption values among students at the elementary and junior high school levels, in order to prevent corrupt practices across various sectors in the future. An interactive outreach approach was conducted through group-based classroom sessions involving 128 students, ranging from Grade 1 elementary school to Grade 9 junior high school at Perguruan Advent Parongpong. The activity was carried out in several stages, including program planning, determination of location and target participants, preparation of educational materials, facilitator training, and evaluation conducted both prior to and following the delivery of materials, particularly for 40 junior high school students.The results indicate an increase in the proportion of students categorized as having very high scores, from 2.5% (1 student) to 72.5% (29 students).